THE IMPORTANCE OF FOREST AND LANDSCAPE RESOURCE FOR COMMUNITY AROUND GUNUNG LUMUT PROTECTED FOREST, EAST KALIMANTAN - Murniati Murniati; Michael Padmanaba; Imam Basuki (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2009)
The forest of Gunung Lumut in Pasir District, East Kalimantan was designated for a protection forest in 1983. It is surrounded by 15 villages and one settlement lies inside it. Communities in those villages are dependent upon the landscape and forest resources mainly for non timber forest products. This study was focused on the perception of the communities on the importance of the landscape and forests. The study was conducted in two settlements, located in and outside (near) the protection forest, namely Rantau Layung Village and Mului Sub-Village. Data collection was undertaken through general field observations, key- informant personal interviews and focus group discussions. In Rantau Layung, the most important land type was rice field, whereas in Mului was forest. There were 13 and 14 use categories of landscape resources in Rantau Layung and Mului, respectively, such as food, medicine, constructions and source of income. People in Rantau Layung and Mului ranked plants to be more important than animals. People also considered products from wild resources to be more important than those from cultivated and purchased sources. Communities living in both settlements considered the future uses of forests to be the most important as compared to those of the present and past. They suggested that sungkai (Peronema canescens) and telien (Eusideroxylon zwageri) to be the most important plants while payau (Cervus unicolor) and telaus (Muntiacus muntjak) to be the most important animals. People used the wildlife mainly for food and source of income. They also identified important and potential resources for economic development in the area, i.e. ecotourism and hydro- power for electric generator.